2016
DOI: 10.1038/srep32131
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of salidroside against bone loss via hypoxia-inducible factor-1α pathway-induced angiogenesis

Abstract: Hypoxia-inducible factor (HIF)-1α plays a critical role in coupling angiogenesis with osteogenesis during bone development and regeneration. Salidroside (SAL) has shown anti-hypoxic effects in vitro and in vivo. However, the possible roles of SAL in the prevention of hypoxia-induced osteoporosis have remained unknown. Two osteoblast cell lines, MG-63 and ROB, were employed to evaluate the effects of SAL on cell viability, apoptosis, differentiation and mineralization in vitro. Rats subjected to ovariectomy-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 64 publications
3
35
0
Order By: Relevance
“…Based on these data, we guess that HIF-1α participates in the pathogenesis of FSGS through targeting inflammatory response and oxidative stress [15]. Recently, Li et al [16] have been reported the protective effect of SAL against bone loss via targeting HIF-1α, indicating the possible target of SAL in FSGS. Recently, the phosphatidylinositol 3-kinase (PI3K)/ protein kinase B (Akt) signaling pathway has been shown to positively affect the translational as well as transcriptional initiation of the HIF-1α gene [17].…”
Section: Introductionmentioning
confidence: 99%
“…Based on these data, we guess that HIF-1α participates in the pathogenesis of FSGS through targeting inflammatory response and oxidative stress [15]. Recently, Li et al [16] have been reported the protective effect of SAL against bone loss via targeting HIF-1α, indicating the possible target of SAL in FSGS. Recently, the phosphatidylinositol 3-kinase (PI3K)/ protein kinase B (Akt) signaling pathway has been shown to positively affect the translational as well as transcriptional initiation of the HIF-1α gene [17].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that up‐regulated HIF‐1α activity was linked with reduced the apoptosis of various cell types including cardiomyocytes and human umbilical vein endothelial cells (HUVECs) 12, 13. On the contrary, suppressed HIF‐1α expression was related to reduction in angiogenesis and glycolysis, increase in ROS production and induction of apoptosis or death of endothelial cells, cancer cells and other cell types 14, 15, 16, 17, 18. Taken together, HIF‐1α is a key regulator of endothelium survival under hypoxic condition, and up‐regulation of HIF‐1α might be a key method of protecting endothelial cells from hypoxic injury.…”
Section: Introductionmentioning
confidence: 99%
“…Based on its pharmacological anti-hypoxic and pro-angiogenic effects, salidroside has anti-osteoporotic activity (1,11). Hypoxia or oxidative stress induced osteoblast apoptosis, decreased osteoblast activity, thus leading to a reduction of osteoblastic bone formation and bone loss, which was abrogated by salidroside treatment by enhancing angiogenesis and osteogenesis (1,11).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, salidroside inhibits the development of lipopolysaccharide (LPS)-induced mastitis in mice by attenuating the LPS-triggered activation of NF-κB and MAPKs (6). Owing to its protective effects against oxidative stress, salidroside has exhibited activity against gastric ulcers (8), hydrogen peroxide-induced apoptosis (3), β-amyloid-induced cognitive deficits (9,10), bone loss (1,11) and various cancer types, including bladder cancer (12) and lung cancer (13), demonstrating the potential use of salidroside in inhibiting the development of these diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation